Mobilome of Brevibacterium aurantiacum Sheds Light on Its Genetic Diversity and Its Adaptation to Smear-Ripened Cheeses - Levesque, Sébastien; de Melo, Alessandra G.; Labrie, Simon J.; Moineau, Sylvain (Frontiers in Microbiology, 2019)
Brevibacterium aurantiacum is an actinobacterium that confers key organoleptic properties to washed-rind cheeses during the ripening process. Although this industrially relevant species has been gaining an increasing attention in the past years, its genome plasticity is still understudied due to the unavailability of complete genomic sequences. To add insights on the mobilome of this group, we sequenced the complete genomes of five dairy Brevibacterium strains and one non-dairy strain using PacBio RSII. We performed phylogenetic and pan-genome analyses, including comparisons with other publicly available Brevibacterium genomic sequences. Our phylogenetic analysis revealed that these five dairy strains, previously identified as B. linens, belong instead to the B. aurantiacum species. A high number of transposases and integrases were observed in the Brevibacterium spp. strains. In addition, we identified 14 and 12 new insertion sequences in B. aurantiacum and B. linens genomes, respectively. Several stretches of homologous DNA sequences were also found between B. aurantiacum and other cheese rind actinobacteria, suggesting horizontal gene transfer (HGT). A HGT region from an iRon Uptake/Siderophore Transport Island (RUSTI) and an iron uptake composite transposon were found in five B. aurantiacum genomes. These findings suggest that low iron availability in milk is a driving force in the adaptation of this bacterial species to this niche. Moreover, the exchange of iron uptake systems suggests cooperative evolution between cheese rind actinobacteria. We also demonstrated that the integrative and conjugative element BreLI (Brevibacterium Lanthipeptide Island) can excise from B. aurantiacum SMQ-1417 chromosome. Our comparative genomic analysis suggests that mobile genetic elements played an important role in​ the adaptation of B. aurantiacum to cheese ecosystems.